Utilization of Methionine Sources for Growth and Met+Cys Deposition in Broilers - Andreas Lemme; Victor Naranjo; Juliano Cesar de Paula Dorigam (Animals, 2020)
Knowledge about the nutritional value of methionine sources is highly important for their appropriate application in terms of animal and economic performance. Therefore, a broiler feeding trial was conducted to determine the relative bioavailability value (RBV) of DL-2-hydroxy-4-methylthio butanoic acid (HMTBA) compared to DL-methionine (DLM). DLM diluted to 65% purity (DLM65) served as the internal standard, with a known RBV of 65%. A total of 1920 d-old male broilers were used in the three-phase feeding trial comprising 16 treatments including a basal, Met+Cys-deficient diet and 5 graded DLM, HMTBA, or DLM65 levels. Growth performance and carcass quality data were subjected to multi-exponential regression analysis. Increasing levels of any Met source significantly improved all performance parameters compared to the negative control (p < 0.05). Across all performance parameters, the RBV of HMTBA was 63% and that of DLM65 was 58%. All RBV estimates of HMTBA and DLM65 were significantly lower than 88% (p < 0.05). Cumulative efficiency of DLM for Met+Cys deposition in body protein was higher than that of HMBTA at any dose, confirming the determined RBV. Using DLM65 as an internal marker allowed for validation of the methodology.